Freezing and thawing of processed meat in an industrial freezing tunnel - Marini, Glaucio Antonio (2014)
Freezing is a commonly used preservation method in the meat industry. The understanding of the product behavior during the freezing process can assist in a better process management and quality control. This work reports the study of freezing and thawing of three types of processed meat in order to determine process parameters in an industrial forced‑air freezing tunnel at ‑30oC. Chicken sausages (frankfurter type), mortadela (bologna type) and mechanically deboned chicken meat (MDCM) were studied. Products were placed in several layers in corrugated cardboard boxes (CCB) for sausages and mortadela. MDCM was placed in a nylon box. Temperature sensors were inserted in the products and the freezing and thawing curves were obtained. Freezing curves were used to determine the freezing time (tf), initial freezing point (Tf) and final freezing point (T’m). Products placed in different layers in the CCB had significantly different freezing times, being the higher rates for products placed in more external layers than internal ones. The external layers of product were subjected to heat transfer by convection showing its importance to decrease freezing time. The results strongly suggest that products placed in different layers could have distinct quality properties and also play a key role in the freezing process efficiency.